Die Vielfalt des "New Regionalism". Communitarian, Civic and Creative Governance-Ansätze für die Steuerung und Integration von US-amerikanischen Stadtregionen. - Blatter, Joachim (TH Zürich, NSL, 2006)
Das Ziel des Beitrages ist es, die wichtigsten - von Praktikern und Wissenschaftlern entwickelten - konzeptionellen Ansätze zur Reform der Metropolitan Governance zu beschreiben und die Argumentationsmuster zu analysieren, um die bisher unterdifferenzierte Beschreibung des New Metropolitan Regionalism zu verbessern. Es werden drei verschiedene Ausprägungen des New Regionalism skizziert, die mit unterschiedlichen Governance-Formen in Verbindung gesetzt werden: Communitarian Governance, Civic Governance, Creative Governance. Anschliessend wird kurz auf die Realisierung der verschiedenen Ansätze eingegangen und es werden Schlussfolgerungen für die wissenschaftliche Debatte gezogen. goj/difu

Since the 1990s, a new metropolitan regionalism has stimulated many reform attempts in the United States to change or introduce new forms of metropolitan governance. The article aims to provide a differentiated view on the goals and governance concepts within the latest wave of metropolitan governance reforms. Three different concepts can be identified: first, a "communitarian governance" approach perceives the socio-spatial segregation as the most pressing problem and tries to gain political majorities through a reconstruction of formal institutions, local interests and mobilizing values. Second, a "civic governance" approach aim, at sustainable development and advocates deliberative forums in order to stimulate cross -functional learning and to reach a consensus for joint development plains and regulations. The third approach is called "creative governance" and focuses on economic competitiveness. The advocates within this camp propose the building of synergetic exchange networks between private and public actors in order to create innovative projects and an attractive image for the city-region. The implementation of these three approaches has been very uneven. Whereas the communitarian governance approach failed even under the most favourable conditions, the civic governance approach has been partly implemented in many regions as a result of a strong anti-sprawl movement. In most metropolitan areas, only the creative governance approach, backed by powerful urban regimes, has been able to challenge and complement the dominance of localism and functional differentiation that has traditionally characterized US metropolitan governance and that is legitimized by various strands of the public choice theory. difu
Keywords: Raumordnung; Raumplanung; Großstadt; Stadtregion; Planungstheorie; Raumordnungspolitik; Planungspraxis; Politikwissenschaft; Agglomeration; Ballungsraum; Governance; Local Governance; Civic Governance; Metropolregion